ESR and U-Th dating results for Last Interglacial coral reef terraces at the northern coast of Cuba. (10th August 2020) - Schielein, Patrick; Burow, Christoph; Pajon, Jesus; Rojas Consuegra, Reinaldo; Zhao, Jian-xin; Schellmann, Gerhard
Abstract: Fossil coral reef terraces at the northern coast of Cuba in the vicinity of the Bay of Matanzas are forming a prominent flight of terraces. These terraces were already studied by several investigators, but a chronological classification based on numerical dating is still missing. In this study we focus on the lowest unit, the Seboruco terrace, which is assumed to be of MIS 5e age. The morphology of the Seboruco terrace and associated sea-level markers (reef crests and notches) were mapped and their altitude was measured over the whole study area in the field and by using remote sensing. The fossil corals building up the terrace were surveyed in numerous natural outcrops. The species of the fossil coral reefs were determined and subdivided in different facies zones. Fossil corals were taken for numerical dating by Electron Spin Resonance (ESR) and Uranium-series (U-Th) to establish a chronology of the MIS 5e coral reef formation. Both dating techniques yielded age results in good agreement with each other and the stratigraphic context. Corresponding to the field evidence, the age data indicates one MIS 5e sea-level highstand around 126 ka. Some younger ESR ages may be explained by the recrystallization of aragonitic corals and/or by U leaching. At one locality east of Matanzas, the radiometric results for an underlying coral reef body suggest an MIS 7 age. The sea-level markers for the MIS 5e highstand range from 5.5 m a.s.l. (reef crest) to a maximum of 7 m (notches) west of the Bay of Matanzas resulting in relatively low uplift rates of 0.003 m/ka and 0.036 m/ka when applying early MIS 5e sea-level estimates from tectonically stable coasts in the Caribbean between +2.5 m and +6.6 m. Inside the Bay of Matanzas itself, the elevation of sea-level markers increases to more than 10 m a.s.l. indicating a stronger uplift rate of 0.027 m/ka to 0.060 m/ka here.